Helicobacter bilis Contributes to the Occurrence of Inflammatory Bowel Disease by Inducing Host Immune Disorders. (9th August 2022) - Peng, Wei; Zhao, Xinhua; Li, Xiaoan
Abstract : Gut microbiota coevolve with humans to achieve a symbiotic relationship, which ultimately leads to physiological homeostasis. A variety of diseases can occur once this balance is disrupted. Helicobacter bilis ( H. bilis ) is an opportunistic pathogen in humans, triggering multiple diseases, including inflammatory bowel disease (IBD). IBD is a chronic immunologically mediated inflammation of the human gastrointestinal tract, and its occurrence is closely related to the gut microbiota. Several studies have demonstrated that H. bilis colonization is associated with IBD, and its mechanism is related to host immunity. However, few studies have investigated these mechanisms of action. Therefore, this article is aimed at reviewing these studies and summarizing the mechanisms of H. bilis -induced IBD from two perspectives: adaptive immunity and innate immunity. Furthermore, this study provides a preliminary discussion on treating H. bilis -related IBD. In addition, we also demonstrated that H. bilis played an important role in promoting the carcinogenesis of IBD and discussed its mechanism.